Molecular Signaling Pathways as Potential Therapeutic Targets in Osteosarcoma - Dana, Parisa M.; Sadoughi, Fatemeh; Asemi, Zatollah; Yousefi, Bahman (Current Medicinal Chemistry, 2022)
Among primary bone malignancies, osteosarcoma (OS) is the most common form causing morbidity and mortality in both adults and children. The interesting point about this malignancy is that nearly 10-20% of its newly diagnosed cases have developed metastasis. This adds up to the fact that the survival rate of both metastatic and non-metastatic patients of osteosarcoma has not changed in the past 30 years; therefore, it has been suggested that we need to revise our therapeutic options for OS. In recent years, diverse signaling pathways have drawn the attention of the scientific community since they can be great candidates for treating complicated diseases, such as cancer. In this review, we have tried to explain the pathophysiology of osteosarcoma with the help of different signaling pathways taking part in its initiation/progression and explore how this pathway can be targeted for providing more efficient methods.
Keywords: MAPK